Disintegration of simulated drinking water biofilms with arrays of microchannel plasma jets. (December 2018) - Sun, Peter; Araud, Elbashir; Huang, Conghui; Shen, Yun; Monroy, Guillermo; Zhong, Shengyun; Tong, Zikang; Boppart, Stephen; Eden, J.; Nguyen, Thanh
Abstract Biofilms exist and thrive within drinking water distribution networks, and can present human health concerns. Exposure of simulated drinking water biofilms, grown from groundwater, to a 9 × 9 array of microchannel plasma jets has the effect of severely eroding the biofilm and deactivating the organisms they harbor.In-situ measurements of biofilm structure and thickness with an optical coherence tomography (OCT) system show the biofilm thickness to fall from 122 ± 17 µm to 55 ± 13 µm after 15 min. of exposure of the biofilm to the microplasma column array, when the plasmas are dissipating a power density of 58 W/cm2 . All biofilms investigated vanish with 20 min. of exposure. Confocal laser scanning microscopy (CLSM) demonstrates that the number of living cells in the biofilms declines by more than 93% with 15 min. of biofilm exposure to the plasma arrays. Concentrations of several oxygen-bearing species, generated by the plasma array, were found to be 0.4–21 nM/s for the hydroxyl radical (OH), 85–396 nM/s for the1 O2 excited molecule, 98–280 µM for H2 O2, and 24–42 µM for O3 when the power density delivered to the array was varied between 3.6 W/cm2 and 79 W/cm2 . The data presented here demonstrate the potential of microplasma arrays as a tool for controlling, through non-thermal disruption and removal, mixed-species biofilms prevalent in commercial and residential water systems. Drinking water: fighting biofilms with plasma jets Biofilms in drinking water premise plumbing systems can be disrupted and their microorganisms deactivated by exposure to jets of ionized gas known as plasma. Researchers at the University of Illinois, USA, led by Thanh (Helen) Nguyen and J. Gary Eden, explored the potential of low temperature plasma jets in disrupting & removing drinking water biofilms. The plasma was directed through fabricated microchannels and onto samples that the simulated biofilms. The interaction of the plasma with air and water generated reactive chemical species and ultraviolet radiation that disrupted the biofilms and deactivated the microorganisms within them. The biofilms studied vanished within 20 min. of plasma exposure. Plasma jets offer an inexpensive, low temperature and chlorine-free method for combating harmful biofilms in drinking water premise plumbing systems.